2022
DOI: 10.1128/spectrum.01077-22
|View full text |Cite
|
Sign up to set email alerts
|

Continued Vaccine Breakthrough Cases of Serotype 3 Complicated Pneumonia in Vaccinated Children, Portugal (2016–2019)

Abstract: The use of conjugate vaccines against Streptococcus pneumoniae in children has led to substantial reductions in pneumococcal invasive disease. However, the reductions seen in each of the 13 serotypes currently included in the highest-valency vaccine approved for use in children (PCV13), were not the same.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 15 publications
1
4
0
1
Order By: Relevance
“…Moreover, concentrations were by far the lowest of the tested serotypes. Since serotype 3 is a main driver of IPD in Germany, these results corroborate the well-known lack of vaccine-protection [37][38][39]. However, for a more accurate assessment of this problem, a longer follow-up of recipients and larger group of participants are necessary.…”
Section: Discussionsupporting
confidence: 74%
“…Moreover, concentrations were by far the lowest of the tested serotypes. Since serotype 3 is a main driver of IPD in Germany, these results corroborate the well-known lack of vaccine-protection [37][38][39]. However, for a more accurate assessment of this problem, a longer follow-up of recipients and larger group of participants are necessary.…”
Section: Discussionsupporting
confidence: 74%
“…Similarly, Silva-Costa et al showed 87/98 (89%) of S . pneumoniae cases were only identified using PCR [ 23 ]. Reliance on culture-based methods for empyema diagnostics may therefore substantially underestimate S .…”
Section: Discussionmentioning
confidence: 99%
“…However, IPDs and AOMs replaced by non-vaccine serotypes including those associated to antibiotic resistance have emerged and now predominate in high-income countries (de Miguel et al 2021 ; Sempere et al 2022 ; Pichichero et al 2023 ). To date, S. pneumoniae still remains a major cause of serious human disease not only in the elderly (de Miguel et al 2021 ), but also in the pediatric population where it associates with complicated pneumonia cases, often with empyema or pleural effusion (Silva-Costa et al 2022 ). Moreover, recent results have demonstrated that serotype 3 pneumococci may cause adverse cardiovascular events during IPD (Africano et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%